Assessment of hydrocarbons subsoil and groundwater pollution in a refinery occupied property at the old industrial zone of Athens - Pireaus, Greece - Zotiadis, V.; Kollios, A. (Bulletin of the Geological Society of Greece, 2007)
Industrial activities that took place in the old industrial zone of Athens-Piraeus widespread pollution in natural systems. This specific environmental site assessment presents subsoil and groundwater pollution data by petroleum hydrocarbons in a property occupied by a small scale refinery the last 50 years. Additionally the vertical distribution and horizontal variability of pollution is analysed as a result of several point sources existence such as underground storage tanL·. Environmental survey site works conducted by boreholes performance and installation of stand-pipe type piezometers for groundwater monitoring. Totally 32 soil core samples were analyzed for total petroleum hydrocarbons and additionally 4 soil core sub-samples where volatile organic compounds maximum values were recorded, analyzed for aromatic hydrocarbons. Petroleum hydrocarbons values in subsoil and groundwater range from 310 to 8130 mgKg1 and 0.6 to 2550 mg/l respectively. This paper provides hydrocarbons pollution data of the site and demonstrates the need for an environmental site assessment study before any investment and development action takes place in brownfield’s areas